Toxicity of urban air pollution particulate matter in developing and adult mouse brain: Comparison of total and filter-eluted nanoparticles. (March 2020) - Haghani, Amin; Johnson, Richard; Safi, Nikoo; Zhang, Hongqiao; Thorwald, Max; Mousavi, Amirhosein; Woodward, Nicholas C.; Shirmohammadi, Farimah; Coussa, Valerio; Wise, John P.; Forman, Henry Jay; Sioutas, Constantinos; et al.
Graphical abstract: Highlights: Filter-eluted nanoparticles (nPM) are depleted in PAH and transition metals compared to total nanoparticles (sPM). Inhalation of nPM and sPM caused comparable neurotoxic reactions in adult and developing brain. Gestational exposure to nPM or sPM caused depressive behaviors in adults. Gestational exposure to sPM caused glutamatergic changes in adults. Abstract: Air pollution (AirP) is associated with many neurodevelopmental and neurological disorders in human populations. Rodent models show similar neurotoxic effects of AirP particulate matter (PM) collected by different methods or from various sources. However, controversies continue on the identity of the specific neurotoxic components and mechanisms of neurotoxicity. We collected urban PM by two modes at the same site and time: direct collection as an aqueous slurry (sPM) versus a nano-sized sub-fraction of PM0.2 that was eluted from filters (nPM). The nPM lacks water-insoluble PAHs (polycyclic aromatic hydrocarbons) and is depleted by >50% in bioactive metals (e.g., copper, iron, nickel), inorganic ions, black carbon, and other organic compounds. Three biological models were used: in vivo exposure of adult male mice to re-aerosolized nPM and sPM for 3 weeks, gestational exposure, and glial cell cultures. In contrast to larger inflammatory responses of sPM in vitro, cerebral cortex responses of mice to sPM and nPM largely overlapped for adult and gestational exposures. Adult brain responses included induction of IFNγ and NF-κB. Gestational exposure to nPM and sPM caused equivalent depressive behaviors. Responses to nPM and sPM diverged for cerebral cortex glutamate receptor mRNA, systemic fat gain and insulin resistance. The shared toxic responses of sPM with nPM may arise from shared transition metals and organics. In contrast, gestational exposure to sPM but not nPM, decreased glutamatergic mRNAs, which may be attributed to PAHs. We discuss potential mechanisms in the overlap between nPM and sPM despite major differences in bulk chemical composition.